2017
DOI: 10.3832/ifor1974-009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of altitudinal gradients on leaf area index, soil microbial biomass C and microbial activity in a temperate mixed forest ecosystem of Northwestern Turkey

Abstract: A high leaf area index (LAI) can provide indications of high fertility, such as optimal health and productivity in forest ecosystem. Yet, studying the microbial biomass and inherent activity in any forest ecosystem may enable better understanding of the role of microorganisms in soil quality and nutrient cycling. This study was carried out in the western Black Sea region of Turkey with the aim to determine the influence of elevation on LAI, microbial biomass and activity in a mixed forest ecosystem. Marked dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
4
2
Order By: Relevance
“…An increase in the total amount of C mic was observed in all areas, more in the burned areas, likely due to the higher amount of rainfall between Months 12 and 24. We found a negative correlation between C mic and qCO 2 that is inconsistent with the results from previous studies (Wardle & Ghani 1995, Bolat & Oztürk 2017, whereas a positive correlation between C mic and CO 2 evolution was detected. A high qCO 2 indicates the need for restoring the C demand as a result of the microbial biomass depending on the renewal of C lost through respiration (Anderson & Domsch 2010, Bolat & Oztürk 2017.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…An increase in the total amount of C mic was observed in all areas, more in the burned areas, likely due to the higher amount of rainfall between Months 12 and 24. We found a negative correlation between C mic and qCO 2 that is inconsistent with the results from previous studies (Wardle & Ghani 1995, Bolat & Oztürk 2017, whereas a positive correlation between C mic and CO 2 evolution was detected. A high qCO 2 indicates the need for restoring the C demand as a result of the microbial biomass depending on the renewal of C lost through respiration (Anderson & Domsch 2010, Bolat & Oztürk 2017.…”
Section: Discussioncontrasting
confidence: 99%
“…We found a negative correlation between C mic and qCO 2 that is inconsistent with the results from previous studies (Wardle & Ghani 1995, Bolat & Oztürk 2017, whereas a positive correlation between C mic and CO 2 evolution was detected. A high qCO 2 indicates the need for restoring the C demand as a result of the microbial biomass depending on the renewal of C lost through respiration (Anderson & Domsch 2010, Bolat & Oztürk 2017. After a low-intensity prescribed fire in a Picea abies forest, basal respiration diminished while there was a disproportionate decrease in C mic (Pietikäinen & Fritze 1995), which clearly led to higher values of qCO 2 in the burned areas compared to unburned ones (Certini 2005).…”
Section: Discussioncontrasting
confidence: 99%
“…The climatic gradient that occurs over short distances in alpine slopes makes altitude a good proxy for understanding the response of forest soils and their ecosystem services to different climatic conditions [14,15]. Although many studies have been conducted along elevation gradients [16][17][18], only a few of them considered the same vegetation at different elevations [6,19], and considered the C and N forms both in the soil and the soil solution. In the European Alps, Gobiet et al [20], based on 10 global climate models, found that 1500 m a.s.l.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, the LAI can be viewed as an indicator through the C assimilation and vegetation productivity capacity, directly or indirectly affecting the soil CO 2 e ux. On the other hand, it should be noted that LAI has a closely associated with soil temperature and soil moisture, and thus indirectly in uences the R S changes (Bolat & Öztürk, 2017). However, the relationships between soil respiration and LAI are not as stable.…”
Section: Relationships Between Vegetation Characteristics and Total S...mentioning
confidence: 98%